PELATIHAN PEMBUATAN WEBLOG SEBAGAI MEDIA ALTERNATIF PEMBELAJARAN ONLINE BAGI GURU-GURU SEKOLAH TUNAS BANGSA KUPANG - Petrus Ana Andung; Yermia Djefri Manafe; Yohanes K.N. Liliwery; Mariana A.N. Letuna; Silvania S.E. Mandaru; Maria Yulita Nara; Muhammad Aslam; Emanuael S. Leuape (Unika Santu Paulus Ruteng, 2022)
The results of need assessment and situation analysis found that the teachers of the Tunas Bangsa Christian Community School Kupang had limited knowledge and skills in using Weblogs as an alternative media for online-based learning. Therefore, the purpose of community service activities was to increase the knowledge and skills of the teachers on how to create and use weblogs for online learning. The PKM method used training and also mentoring. The results of this activity indicated an increased understanding of the teachers of the school regarding the importance of using the WordPress media platform as an alternative learning media to support online learning. This was indicated by an increase in teacher knowledge based on the results of the comparison of participants' reflection scores before and after the training. In addition, teachers also experienced an increase in knowledge and skills in creating or designing WordPress as a teacher's personal website in order to publish various articles, assignments, materials, and others related to learning at school